A Biomechanical Analysis of Wide, Medium, and Narrow Grip Width Effects on Kinematics, Horizontal Kinetics, and Muscle Activity on the Sticking Region in Recreationally Trained Males During 1-RM Bench Pressing - Larsen, Stian; Gomo, Olav; van den Tillaar, Roland (Frontiers in Sports and Active Living, 2021)
Grip width has been found to affect lifting performance, especially around the sticking region; however, little is known about the kinetics and muscle activities that could explain these differences in performance. This study aimed to investigate the effects of grip width on the joint, barbell kinematics, and horizontal kinetics, analysed in tandem with the effects of muscle activation around the sticking region in the one repetition maximum (1-RM) barbell bench press. Fourteen healthy bench press-trained males (body mass: 87.8 ± 18.4, age: 25 ± 5.2.4) performed 1-RM with a small, medium, and wide grip width. The participants bench pressed 109.8 ± 24.5 kg, 108.9 ± 26.4 kg, and 103.7 ± 24 kg with the wide, medium, and narrow grip widths. Furthermore, the wide grip width produced 13.1–15.7% lateral forces, while the medium and narrow grip widths produced 0.4–1.8% and 8.5–10.1% medially directed forces of the vertical force produced during the sticking region respectively. Horizontal forces did not increase during the sticking region, and the resultant forces decreased during the sticking region for all grip widths. The wide and medium grip widths produced greater horizontal shoulder moments than the narrow grip width during the sticking region. Hence, the wide and medium grip widths produced similar shoulder and elbow joint moments and moment arm at the first located lowest barbell velocity. Furthermore, triceps medialis muscle activity was greater for the medium and narrow grip widths than the wide grip width. This study suggests that the sticking region for the wide and medium grip widths may be specific to the horizontal elbow and shoulder joint moments created during this region. Therefore, when the goal is to lift as much as possible during 1-RM bench press attempts among recreationally trained males, our findings suggest that bench pressing with a wide or medium grip width may be beneficial.